The influence of physical activity on immunity - Mazić, Sanja; Djelić, Marina (Archives of Pharmacy, 2022)
Response of the immune system depends primarily on the intensity of physical activity. Infections of the upper respiratory tract are 2-6 times more common in elite athletes compared to the general population, especially during intensive training. It has been shown that vigorous physical activity can lead to a decrease in the activity of B and T lymphocytes and an increase in the level of the stress hormones adrenaline and cortisol, as well as the level of free radicals. There is also a decrease in the level of IgA, which protects the gastrointestinal and respiratory tract from viral infections. At the beginning of this century with the discovery of numerous cytokines, studies have confirmed that 60 minutes of moderate aerobic exercise, at least three times a week, enhance our immunity in the following ways: deepens breathing and consequently the chance to expel microorganisms from the respiratory tract, increases activation and secretion of immunoglobulins and cytokines, accelerates the circulation of blood and lymph through muscle contractions, and in this way, neutrophils and lymphocytes reach the microorganisms faster. Also, regular physical activity increases the number of CD4+T cells, which are responsible for alerting the immune system to an "outside" attack and for regulating its reaction to bacteria and viruses. Studies have shown over 100 times increase in IL-6 compared to resting values ​​after exhausting physical activity such as the marathon race, and this response can last up to 72 hours of recovery, thus confirming and indicating systemic inflammation during vigorous physical activity.